Assessment of BCL-2 expression in actinic keratosis, keratoacanthoma and seborrheic keratosis cases (Annals of Medical Research, 2021)
None
Keywords: Mesenteric Vascular Occlusion; Surgery; Endovascular Procedures; Morbidity, Mortality.